(untitled) (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES RESEARCH AND DEVELOPMENT (IJSSRD), 2024)
The 2023/2024 War on Gaza, despite its many challenges, has illuminated unique opportunities for the Free-Palestine cause, particularly the potential for influence without formal power. This paper explores the emergence of 'live models' who have exemplified resilience and ingenuity in breaking the blockade around Gaza, inspiring individuals and communities all over the world to engage and contribute meaningfully. This paper explores how influence can be cultivated with soft power through storytelling, community engagement, and leveraging fundamental human values. Sharing experiences and challenges relevant to the War on Gaza can create ripple effects, motivating others and strengthening grassroots movements. The war has also underscored the importance of empowering community members through building cross-generational connections and social media advocacy, so that they can act as ambassadors for the Palestinian Cause even beyond the war on Gaza 2023/2024. The researcher examines how Gaza's resilience lab supports creating waves of ‘influence without power’, through basic formulas that bring simple solutions for Gaza’s basic needs that are even alarming with the limitation of health services, and infrastructure destruction, besides the socio-political and socioeconomic challenges. The formulas guide impactful change and foster a more profound, sustained support for Gaza and the broader Free-Palestine movement.